Analisis Transparansi dan Akuntabilitas Pengelolaan Dana Zakat Yayasan Dana Sosial - Khumairoh, Dzurorin; Rahman, Taufiqur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research is motivated by several studies stating that transparency and accountability in the management of zakat funds have a positive correlation with the trust of the muzakki. However, understanding regarding the effectiveness of fund utilization, program sustainability, and openness in reporting is still limited. This study aims to fill this gap by analyzing these aspects to provide a comprehensive overview of the implementation of transparency and accountability in the management of zakat funds at LAZNAS Yayasan Dana Sosial Al-Falah Surabaya. The method used is descriptive analysis, data collected through semi-structured interviews, documentation, and observation. Data analysis techniques in this study involve data reduction, data presentation, and conclusion drawing processes. The research results show that Yayasan Dana Sosial Al-Falah Surabaya has successfully implemented the principles of transparency and accountability. Transparency is evidenced by the ease of accessing all information regarding financial reports and implemented programs. Meanwhile, in terms of accountability, Yayasan Dana Sosial Al-Falah Surabaya demonstrates compliance with the procedures for preparing financial statements in accordance with the principles of the Financial Accounting Standards (PSAK) 109.